PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA SEKTOR PROPERTI, REAL ESTATE, DAN KONSTRUKSI - Andreini, Raya Mercury; Safrida, Lili (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2023)
This research aims to determine the effect of profitability, liquidity, leverage, activity, and sales growth on financial distress. This research was quantitative research with logistic regression as a data analysis technique. The research samples were 61 companies from the Property, Real Estate, and Construction Sectors listed on IDX in the 2018-2020 periods which were selected using the purposive sampling method. The results showed that profitability, liquidity, and activity significantly affected financial distress. Meanwhile, leverage and sales growth had an insignificant effect on financial distress. Therefore, companies as well as investors and creditors should consider financial ratios, especially profitability, liquidity, and activity as information material in assessing the company's financial distress condition.Keywords: Activity; Financial Distress; Leverage; Liquidity; Profitability; Sales Growth